Best practice of conflict management among principals of excellent secondary schools, Malaysia - Salleh, Mohamad Johdi; Safarali, Kadamov (2015)
This study discusses the best practice of conflict management among principals of Excellent Secondary Schools, Malaysia. The study involved 1020 respondents comprises seniorteachers, teacher-administrators, teachers, and, counsellors. The instrument used was survey questionnaire and data was processed using the Statistical Package for Social Science version 16.0 for Windows. The study was mainly based on Rahim (2001) and Thomas and Kilmann (2008) conflict-handling modes. The findings of the study indicate that the best practice of conflict management among principals of Excellent Secondary Schools in Malaysia was on domain ‘Collaborating’ with mean 4.1434, the second highest was ’Compromising’ with mean 3.8834 and the third highest was ’Empowerment’ with mean 3.8400. It is hoped that the findings of this study may guide the principals, teacher-administrators, educational leaders, teachers, and all groups or individuals in educational organizations to manage conflicts wisely and successfully towards the harmonious working environment with optimum productivity towards realisation of Malaysia Education Blueprint 2013-2025.